Pandangan Filsafat Hukum Terkait dengan Etika Profesi - Adityadarma Bagus Priasmoro Suryono; Dona Sri Sunardi Wijayanti; Irene Fransisca Liemanto; Qonrezti Shebilla Kalia; Andika Cahyo Bintoro (Jurnal Hukum Lex Generalis, 2020)
Some examples of cases of client neglect by rogue advocates or black advocates are a reflection that the arrangements regarding the code of ethics for the advocate profession in Indonesia have not worked as they should. This becomes the initial urgency that professional ethics is an important role in the enforcement of discipline, honor and dignity of a profession in general, both associations and individuals who work as advocates. Then, the code of ethics as a form of professional ethics not only stops at the level of thought and theory, but also must be applied practically in the field. Professional ethics according to a comprehensive study of legal philosophy is needed to uphold the spirit of the advocate profession both from upstream to downstream, especially when discussing morality. In this paper, the author takes the example of Joko Sriwidodo as an illustration.